Leptin serum concentrations are associated with weight gain during lithium augmentation. (September 2016) - Ricken, Roland; Bopp, Sandra; Schlattmann, Peter; Himmerich, Hubertus; Bschor, Tom; Richter, Christoph; Stamm, Thomas J.; Bauer, Frank; Heinz, Andreas; Hellweg, Rainer; Lang, Undine E.; Adli, Mazda
Highlights: First study investigating weight-gain and leptin during lithium augmentation (LA). Leptin and body-mass-index (BMI) measured in a prospective cohort study (n = 89). During LA BMI increases and leptin has a positive effect on BMI. Leptin signalling might be involved in lithium-induced weight gain. Abstract: Background: Meta-analytical data show lithium augmentation (LA) as an effective treatment strategy in major depression. Weight-gain is a common side effect of LA. The proteohormone leptin is discussed to be involved in the pathophysiology of weight gain induced by psychopharmacological treatment. The purpose of our study was to investigate the association of leptin and body mass index (BMI) during LA in a prospective cohort study. Methods: Leptin serum concentrations and body mass index (BMI) were measured in a total of 89 acute depressive patients before and then after four weeks of LA. Results: In a linear mixed model analysis the following variables had a significant positive effect on BMI: time (equal with "treatment effect of LA"; F1.83 = 6.05; p = 0.016) and leptin (F1.111 = 13.83; p = 0.0003) as well as the covariates male gender (F1.89 = 5.08; p = 0.027) and adiposity (F1.85 = 105.13; p<0.0001). Limitations: If the reported effect of leptin on BMI is specific to LA remains unclear without a control group. Conclusion: Leptin signalling might be involved in lithium-induced weight-gain.